Dual X-ray Absorbtiometry Can Predict Total and Regional Body Fat Percentage: A Comparative Study With Skinfold Thickness and Body Mass Index For Adult Women: Dual X-ray Absorbtiometry Body Fat Percentage Skinfold Thickness BMI Adult Women - Küçükkubaş, Nigar; Korkusuz, Feza (Progress in Nutrition, 2020)
Background and Purpose: Distribution and volume of total and regional fat and fat percentage is important to monitor diet and exercise in adult women. A prediction formula for adult women by examining Body Mass Index (BMI), quotas obtained from Skinfold Thickness (ST) sites and body composition compartments determined by using Dual X-ray Absorptiometry (DXA) was aimed. Participants and Method: Sixty female participants (average age 46.4 ± 3.2 years; Range 40 - 55 years) were assessed by using DXA (Lunar Model DPX) to determine body fat percentage (%BFDXA), Fat Mass (FMDXA), and Lean Body Mass (LBMDXA). Skinfold thickness sites were measured by using Skinfold Caliper (Holtain Caliper, UK). Results: A low positive correlation coefficients was found between %BF obtained from DXA and quota of suprailium ST (r=0.30 p